Economic growth and measurement reconsidered in Botswana, Kenya, Tanzania, and Zambia, 1965-1995 - Jerven, Morten (Oxford Oxford University Press, 2014)
How do we measure African economic performance? This volume studies how growth is measured in Botswana, Kenya, Tanzania and Zambia and challenges commonly held beliefs of African economic performance.
Includes bibliographical references and index.
Keywords: Economic development--Africa, Sub-Saharan.